Inequality and the family - Singapore Management University (Institutional Knowledge at Singapore Management University, 2022)
It may be near impossible to recreate Lareau’s “concerted cultivation” outside a middle-class family but intervention targeted at a wider audience – instead of means testing – could ameliorate inequality reproduction